Meduza, osłona i wysłannik niebios. Tajemnice Pieśni IX „Piekła” Dantego według nadinterpretacji Giulia Leoniego w powieści „I delitti dellaMedusa” - Raczyńska, Alicja (Studia Europaea Gnesnensia, 2015)
Giulio Leoni, a modern Italian writer, is the author of five crime novels inspired by the life and works of Dante Alighieri. He presents Dante as a detective who investigates mysterious crimes of the early 14th-century Florence, Rome and Venice. Although Leoni has gained an international fame, there are very few studies which examine the connections between the “Divine Comedy” and his books. My article aims to analyze the overinterpretation of Canto IX of the “Inferno” in the novel “I delitti della Medusa”.